Effects of Compudose® and Ralgro® implants and Tramisol® injectable wormer on the performance of grazing yearling steers - S. Laudert; C. Sauerwein; G. Harris (Kansas Agricultural Experiment Station Research Reports, 1983)
Compudose and Ralgro improved (P<.05) average daily gain 15% over non-implanted controls. No difference was observed between the two implants. Tramisol injectable wormer increased (P<.05) average daily gain 8% over non-wormed cattle.
Keywords: Cattlemen' s Day; 1983; Report of progress (Kansas State University. Agricultural Experiment Station); 427; Beef; Implants; Performance; Steers